Equality within Our Lifetimes How Laws and Policies Can Close-or Widen-Gender Gaps in Economies Worldwide - Heymann, Jody (University of California Press, 2023)
Well into the twenty-first century, achieving gender equality in the economy remains unfinished business. Worldwide, women's employment, income, and leadership opportunities lag men's. Building and using a one-of-a-kind database that covers 193 countries, this book systematically analyzes how far we've come and how far we have to go in adopting evidence-based solutions to close the gaps. Spanning topics including girls' education, employment discrimination of all kinds, sexual harassment, and caregiving needs across the life course, the authors bring the findings to life through global maps, stories of laws' impact in courts and beyond, and case studies of making change. A powerful call to action, Equality within Our Lifetimes reveals how gender equality is both feasible and urgently needed to address some of the greatest challenges of our generation. "An inspirational title to further the advancement of comprehensive gender equality, which goes beyond formal and protective equality to substantive equality that underpins transformative laws, policies, and, above all, results on the ground." - VIRGINIA BRAS GOMES, Former Chairperson of the UN Committee on Economic, Social and Cultural Rights "This book makes a compelling case, based on both quantitative and qualitative data, for how and why gender equality benefits everyone. Governments would be wise to heed this lesson." - YASMEEN HASSAN, Global Executive Director, Equality Now "This book is an essential handbook for those invested in gender equality law and policy." - CATHERINE FISK, Barbara Nachtrieb Armstrong Professor of Law, University of California, Berkeley School of Law